Effect of laser shock peening on residual stress of 316L stainless steel laser metal deposition part - Peng Xu; Cong Chen; Hongxuan Sun; Yi Zhang (Journal of Materials Research and Technology, 2025)
In order to improve the residual stress of laser metal deposition (LMD) parts and ensure that the components are in a state of compressive or zero residual stress, laser shock peening (LSP) is applied to the surface of the parts. LMD experiments were conducted, and LSP was applied to LMD parts of different thicknesses. A 3D finite element model combining LMD and LSP processes was developed for 316L stainless steel using Abaqus. The residual stress distribution of the parts after LMD and LSP was obtained, and the influence of LSP on the residual stress of LMD parts was investigated. The effect of LSP on the improvement of residual stress in LMD parts of different thicknesses was compared. The accuracy of the model's residual stress predictions was validated. The results show that after LSP process, the tensile stress at the top of the LMD part is converted into compressive stress. However, beyond a certain depth, the residual stress reverts to tensile stress. The best improvement in residual stress is observed in the 4-layer LMD part. The study proposes the optimal number of LMD layers to improve the residual stress of 316L stainless steel LMD parts through LSP and provides theoretical guidance for predicting the residual stress of LMD parts after LSP using numerical simulation methods.